The soul of the child : nurturing the divine identity of our children - Gurian, Michael (New York : Atria Books, 2002)
Michael Gurian combines analysis of science with the study of spiritual texts to explore the divine side of childhood, and to put forth a practical design for the care of children's souls. Blending stories, common sense, and scientific observations that demonstrate what the soul is and how it works, this book urges its readers to become aware of children's divine inheritance, and learn how to nurture that divinity.
Includes bibliographical references and index.
Keywords: Parenting -- Religious aspects; Parent and child; Soul